Exploring Lecturers' Perceptions on the Use of Inclusive Pedagogical Strategies in Higher Education Contexts: A Case Study of Lecturers at a Private Higher Education Institution in Johannesburg, South Africa - Chindomu, Rodwell (The IIE, 2020)
Inclusive pedagogy is often narrowly associated with increasing enrolment and access to education for “disadvantaged” groups. This study sought to explore the wider view, which holds that inclusive pedagogy transcends the mere integration of students with disabilities into mainstream institutions or the admission of blacks into formerly white schools and universities. This notion is derived from the argument explored in literature, which purports that presence in an institution alone does not automatically translate to inclusion, as there is a myriad of barriers that limit effective learning for students of diverse dispositions and backgrounds. This research study followed the qualitative paradigm to explore lecturers’ levels of awareness and perceptions of inclusive pedagogy. The study also sought to establish if there was any correlation between lecturers’ perceptions of inclusive pedagogy and their classroom practices. This was done by analysing the participant lecturers’ teaching philosophies, preferred pedagogical strategies and perceptions towards teaching styles, differentiated learning styles, assessment preparation and parental involvement in the teaching and learning process at tertiary level. The results of the study showed that the respondents had varied perceptions on many issues although they converged on the notion that teaching style had an impact on student learning. In the concluding chapter, the thrust of the recommendations was that inclusive pedagogy was not limited to the lecture room, therefore, all stakeholders needed to work together to ensure its success.
Keywords: Inclusive pedagogy; Pedagogical practices; Pedagogical strategies; Teaching philosophy; Teaching style; Learning styles